Outcomes of colonoscopy with non-anesthesiologist-administered propofol (NAAP): an equivalence trial - Alburquerque, Marco; Smarrelli, Antonella; Montesinos, Julio Chevarria; Carreño, Sergi Ortega; Fernandez, Ana Zaragoza; García, Alba Vargas; Frontado, Cesar Ledezma; Vidal, Lluís; Francesch, Montserrat Figa; Lladó, Ferrán González-Huix (Endoscopy International Open, 2021)
Background and study aims Efficacy and safety of NAAP for gastrointestinal endoscopy have been widely documented, although there is no information about the outcomes of colonoscopy when the endoscopist supervises the sedation. In this context, the aim of this trial was to determine the equivalence of adenoma detection rate (ADR) in colorectal cancer (CRC) screening colonoscopies performed with non-anesthesiologist-administered propofol (NAAP) and performed with monitored anesthesia care (MAC).Patients and methods This was a single-blind, non-randomized controlled equivalence trial that enrolled adults from a national CRC screening program (CRCSP). Patients were blindly assigned to undergo either colonoscopy with NAAP or MAC. The main outcome measure was the ADR in CRCSP colonoscopies performed with NAAP.Results We included 315 patients per group. The median age was 59.76 ± 5.81 years; 40.5 % of patients were women. The cecal intubation rate was 97 %, 81.8 % of patients had adequate bowel preparation, withdrawal time was > 6 minutes in 98.7 %, and the median global exploration time was 24.25 ± 8.86 minutes (range, 8–70 minutes). The ADR was 62.9 % and the complication rate (CR) was 0.6 %. Analysis by intention-to-treat showed an ADR in the NAAP group of 64.13 % compared with 61.59 % in the MAC group, a difference (δADR) of 2.54 %, 95 %CI: −0.10 to 0.05. Analysis by per-protocol showed an ADR in the NAAP group of 62.98 %, compared with 61.94 % in the MAC group, δADR: 1.04 %, 95 %CI: −0.09 to 0.07. There was no difference in CR (NAAP: 0,63 vs. MAC: 0.63); P = 1.0. Conclusions ADR in colorectal cancer screening colonoscopies performed with NAAP was equivalent to that in those performed with MAC. Similarly, there was no difference in complication rates.